Higher-level molecular phylogenetic relationships of the endemic genus Lankascincus from Sri Lanka based on nuclear DNA sequences - Austin, Christopher C.; Das, I.; Anslem, de Silva (2004)
The island of Sri Lanka, located off the tip of the Indian peninsula, has an amazingly diverse and highly endemic herpetofaunal assemblage despite its close proximity to the mainland. Lankascincus, a scincid genus endemic to the island of Sri Lanka, is one of the most common skinks found on the island.